Penyakit pada anak sebagai salah satu faktor etiologi molar incisor hypomineralization : scoping review - Azkia Raihani; Enrita Dian Rahmadini; Sri Ratna Laksmiastuti (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Molar incisor hypomineralization is one of the major developmental defects of enamel affecting one or more first permanent molars and is often associated with incisor involvement. MIH is thought to be idiopathic, but the etiology is not yet known. Objective: The aim of this study was to determine the relationship between postnatal factors, namely the disease suffered by children aged 0-3 years and MIH in the group of children aged 6-15 years. Methods: The study was conducted using a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram through databases such as Google Scholar, PubMed, Wiley, and Science Direct using keywords of ((molar incisor hypomineralization) AND (permanent molar)) AND (etiology). Results: 32 articles that fits the criteria were found and were divided into 2 categories, namely: disease in children as a factor for MIH and disease in children associated with MIH. Conclusion: Based on the results of the study, it can be concluded that there is a relationship between disease in children aged 0-3 years and the occurrence of MIH in children aged 6-15 years. Respiratory disease at an early age was associated with the occurrence of MIH most frequently.